กล้วยหอมทองบ้านลาด : ต้นทุนการผลิตกับความคุ้มค่าในการลงทุน - นุชเนตร, อธิสิทธิ์; เพชรัตน์กูล, สุภาพร (JOURNAL OF SOUTHERN TECHNOLOGY, 2013)
การวิจัยครั้งนี้มีวัตถุประสงค์เพื่อศึกษาต้นทุนการผลิต อัตราผลตอบแทน และวิเคราะห์ความเป็นไปได้ และความคุ้มค่าในการลงทุนปลูกกล้วยหอมทองบ้านลาดของเกษตรกร 4 ตำบล คือ ถ้ำรงค์ ไร่สะท้อน ตำหรุ และหนองกระเจ็ด ของอำเภอบ้านลาด จังหวัดเพชรบุรี โดยใช้การวิจัยเชิงปริมาณรวบรวมข้อมูลด้วยแบบสอบถามที่สร้างขึ้นจากการทบทวนวรรณกรรมที่เกี่ยวข้องซึ่งมีค่าความเที่ยงตรง 0.8 โดยรวบรวมจากประชากร จำนวน 81 ครัวเรือน คำนวณต้นทุนและผลตอบแทนเพื่อหาระยะเวลาคืนทุน มูลค่าปัจจุบันสุทธิ และอัตราผลตอบแทนภายใน ใช้อัตราคิดลดร้อยละ 3 เทียบเท่าอัตราดอกเบี้ยเงินกู้ของสหกรณ์การเกษตรบ้านลาด กำหนดอายุโครงการ 3 ปี ผลการวิจัยพบว่า อำเภอบ้านลาด การผลิตและตลาดกล้วยหอมทองของตำบลถ้ำรงค์ให้ผลตอบแทนสูงสุดทั้งปริมาณและมูลค่า มีระยะเวลาคืนทุน 1 ปี 6 เดือน 19 วัน มูลค่าปัจจุบันสุทธิ 1,431,845.62 บาท อัตราผลตอบแทนภายในร้อยละ 42.78 ตำบลหนองกระเจ็ด ระยะคืนทุน 1 ปี 9 เดือน 18 วัน มูลค่าปัจจุบันสุทธิ 734,872.21 บาท อัตราผลตอบแทนภายในร้อยละ 31.42 ตำบลตำหรุ ระยะคืนทุน 2 ปี 2 เดือน 3 วัน มูลค่าปัจจุบันสุทธิ 294,775.16 บาท อัตราผลตอบแทนภายในร้อยละ 18.79 ส่วน ตำบลไร่สะท้อนมีระยะคืนทุนมากกว่า 3 ปี ประสิทธิภาพกล้วยหอมทองอยู่ที่การใช้ปุ๋ยชีวภาพในการผลิตและขายกล้วยหอมทองผ่านสหกรณ์การเกษตรบ้านลาด Kloyhomthongbanlad : Production Cost and Return on Investment The purpose of this research was to study the production cost, rate of return, feasibility and the investment’s worth for Kloyhomthongbanlad of farmers in the sub-district of Tamrong, Raisathon Talu and Nongkrached, Banlad district, Phetchaburi. Eighty one households was surveyed using quantitative data collection with questionnaires that generated from the reviewed relevant literature, which was 0.80 of accuracy. Cost and return were calculated in order to find out the pay back periods, net present value (NPV) and an internal rate of return (IRR) using discount rate which was equivalent to 3 percent interest rate for the loan of the Banlad Agricultural Cooperatives. The project period was 3 years. The results found that, in Banlad district, the highest yield in both quantity and value was Tamrong with the payback period 1 year 6 months 19 days, 1,431, 845.62 Baht of net present value, and internal rate of return 42.78 %. The payback period 1 year 9 months 18 days, 734,872.21 Baht of net present value and internal rate of return 31.42% were Nongkrached. And also, Tamlu got payback period 2 years 2 months 3 days, 294,775.16 Baht net present value and internal rate of return 18.79 %. However, Raisathon returned more than 3 years. The research suggested that efficiency in production was on organic fertilization in the soil maintenance and sale the product through Banlad Agricultural Cooperatives.